2010
DOI: 10.1111/j.1442-2042.2010.02642.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic variables and nomograms for renal cell carcinoma

Abstract: Abstract:The term renal cell carcinoma (RCC) is used to describe a heterogeneous group of tumors that vary histologically, genetically and molecularly. Extensive research has been conducted to identify characteristics that predict outcomes among patients with RCC. In addition to histological subtype these include tumor size, patient age, mode of presentation and various hematological indices, among others. Several groups have incorporated these clinical and pathological features into nomograms which help the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 130 publications
(264 reference statements)
0
23
1
3
Order By: Relevance
“…The best established morphologic prognostic factors include tumor type and stage, presence of sarcomatoid components and for some subtypes, histologic grade [1]. The grading system for CCRCC has been revised recently [8], with necrosis being defined as an additional poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best established morphologic prognostic factors include tumor type and stage, presence of sarcomatoid components and for some subtypes, histologic grade [1]. The grading system for CCRCC has been revised recently [8], with necrosis being defined as an additional poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…This increased interest is partly due to the introduction of new methods of treatment, such as targeted drugs or alternative surgery. Prognostic factors of CCRCC include stage, grade and histologic type; many biomarkers have been studied, but few of them have yet become of any practical importance [1,2]. TP53, possibly the best known tumor suppressor gene, is mutated in over 50% of human cancers, and in some cases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to the canonical classification of ccRCC (Flanigan et al, 2011), the Furhman nuclear grade is one of the most important parameters for RCC prognosis prediction (Nese et al, 2009), together with stage, age, tumor position and size, necrosis and other few molecular biomarkers (e.g., CA9). Noticeably, recent grade-dependent proteomic characterization reported that MYC, HIF-1 and p53 are the major hubs of the network obtained analyzing formalin-fixed paraffin embedded ccRCC tissues (Perroud et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Based on histology, RCC can be classified into several subtypes, i.e., clear cell (80% of cases), papillary (10%), chromophobe (5%) and oncocytoma (5%), each one characterized by specific histopathological features, malignant potential and clinical outcome (Cohen & McGovern, 2005). Patient stratification is normally achieved using prognostic algorithms and nomograms based on multiple clinico-pathological factors such as TNM stage, Fuhrman nuclear grade, tumor size, performance status, necrosis and other hematological indices (Flanigan et al, 2011), although the most efficient predictors of survival and recurrence are based on nuclear grade alone (Nese et al, 2009). As recently reviewed by Brannon et al , a finer RCC subtype classification could be obtained exploiting the vast amount of genomic and transcriptional data that have been presented in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Tamanho tumoral é um componente-chave no sistema de estadiamento TNM, além de ser um dos mais importantes indicadores de prognóstico, devendo ser bem analisado (VOLPE e JEWETT, 2005;POLCARI et al, 2011). Definimos os pontos de corte para análise do tamanho tumoral (≤ 4,0 cm, > 4,0 e ≤ 7,0cm, > 7,0 cm) com base no estadiamento TNM (Anexo B).…”
unclassified